Theory of alternating-current machinery - Langsdorf, Alexander S (McGraw-Hill Book Company, 1955)
Theory of alternating-current machinery / Langsdorf, Alexander S.. -- New York: McGraw-Hill Book Company, 1955 621.3133 L269e2 2nd ed No. of Copies : 1